An Application of Spatial Dispersion Industrialization Model Towards Income Distribution, Employment Opportunity, and Economy - Arie Wahyu Prananta; Zainal Abidin; Syafiyuddin (Journal of Islamic Economics Lariba, 2022)
Industrialization is expected to bring positive impacts for the indigenous people in the form of the emergence of social change. The occurred social change is expected to present sufficient room availability, especially on social income, employment opportunity, and economy. Industrialization consequences lead to spatial dispersion problems, which the policymakers do not expect. The impacts are the emergence of the new social class structure change, the high urbanization flow, life necessity fulfillment competition, and the emerging social gap. This study is expected to discover and develop a spatial dispersion model to focus on the three cities in the industrialization process in terms of income, economy, and employment opportunities. To see the compatibility among the three spatial dispersion indicators (income distribution, employment opportunity, and economy) compared to industrialization, the researchers applied Structural Equation Modeling (SEM) approach to test the hypotheses and analyze the empirical data retrieved through the covariance matrices. The research findings showed the correlation among the three variables by analyzing the retrieved CR values and the probabilities. It can be concluded that income distribution, employment opportunities, and the economy significantly influenced industrialization in Bunder Village, Pademawu Sub-district, Pamekasan Regency. Future research should cover other variables or areas to broaden the insight into how these variables impact industrialization.